A Review of the Research on the Scales for Assessing Emotional Disturbance: Screener. Issue 1 (2nd January 2021) - Lambert, Matthew C.; Garcia, Allen G.; Epstein, Michael H.; Cullinan, Douglas; Martin, Jodie D.
Abstract: The purpose of this article is to provide a qualitative review of the published research on the Scales for Assessing Emotional Disturbance-3: Screener noting the psychometric properties and overall findings. Results from 10 studies were reviewed and summarized. Across the studies, internal consistency, test–retest reliability, and inter-rater agreement were satisfactory. Unidimensionality of the tests scores was supported, and several studies reported only trivial degrees of bias across racial/ethnic and linguistic backgrounds. Diagnostic utility was acceptable as were convergent relations with other measures of psychopathology. Social validity was also satisfactory. This review indicates that the psychometric properties of the scores from the Screener meet acceptable professional standards and supports its use in school-based programs to identify at-risk students.